1969
DOI: 10.1139/v69-162
|View full text |Cite
|
Sign up to set email alerts
|

γ-Radiolysis of disulfides in aqueous solution. II. D-Penicillamine disulfide

Abstract: The γ-radiolysis of D-penicillamine disulfide (PenSSPen) in 3 × 10−4 M aqueous solution has been studied under aerated and deaerated conditions. G values were determined for the following products: penicillamine sulfinic acid (PenSO2H), penicillaminic acid (PenSO3H), β-hydroxyvaline (PenOH), 2-amino-3-methylbut-3-enoic acid (HOOC•CH(NH2)•C(CH3)=CH2), penicillamine (PenSH), penicillamine disulfide-S-monoxide (PenS(O)SPen), valine (PenH), penicillamine trisulfide (PenSSSPen), and ammonia. The low yield of PenSO3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1973
1973
1987
1987

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Samples for product analysis were acidified and run as soon as possible on a Technicon amino acid analyzer, with care being taken to exclude air (16 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples for product analysis were acidified and run as soon as possible on a Technicon amino acid analyzer, with care being taken to exclude air (16 …”
Section: Methodsmentioning
confidence: 99%
“…It appears that trisulfides are formed by more than one pathway. Trisulfides were also obtained in high yield by radiolysis of penicillamine disulfide and cysteine -penicillamine disulfide (16). If RSradicals of penicillamine react with protein disulfide bridges with resultant formation of trisulfides, irreversible damage may be done.…”
Section: Build-up Of Rssr-in Rsh Solutionsmentioning
confidence: 99%
“…respectively, while penicillamine (PenSH) and p-hydroxyvaline (PenOH) were obtained from Koch-Light Laboratories. Penicillamine trisulphide (PenSSSPen) was prepared by the method described by Purdie (1969) and pencillamink acid (PenS03H) was prepared by the Borner (1965) method. All solutions were made using doubly distilled water, the final distillation from alkaline permanganate and the pH adjusted using H2S0,.…”
Section: Methodsmentioning
confidence: 99%
“…Disulfides also produce thiyl radicals during irradiation through their It has been suggested that for disulfides such as cystine or penicill amine, reaction 30 may be quite important [33]. This reaction certainly operates for bis(t-butyl) disulfide in which the t-butyl fragment is relatively stable [71] and contributes to the spectrum of products produced during the Irradiation of cystine [363], penicillamine [364], and cystine-penicillamine mixed disulfide [365]. However, evidence from pulse radiolysis [367] and product analysis [336,337,338,363,364,365] experiments suggests that for many biologically relevant disulfides, reaction 29 predominates.…”
Section: B Thiols and Free Radical Reactionsmentioning
confidence: 99%